Income Polarisation and Poverty Among Rural Households in Nigeria (2013)
Poverty in Nigeria has been on the increase with consequence for Income Polarisation (IP). The IP which is the sum effect of alienation and identification between two groups at polar ends of the income distribution could worsen poverty. Studies on income distribution and poverty have mostly focused on income inequality to the total neglect of IP. Therefore, the extent and pattern of IP and its relationship with poverty among rural households in Nigeria were investigated. Data covering households’ socio-economic characteristics and consumption expenditure were obtained from secondary sources through the National Consumer Survey of 1980, 1985, 1992, 1996 and National Living Standards Survey of 2004 conducted by the National Bureau of Statistics. As a result of data collection and cleaning with elimination of households with some missing values considered important for the study, samples of 4,685, 4,044, 5,712, 11,358 and 22,152 households with relevant variables: household’s consumption expenditure, occupation, gender, education, age, household size and marital status were used for the survey periods. Analysis was done for the six geopolitical zones of rural Nigeria. Data were analysed using Duclos-Esteban-Ray (DER) polarisation index, Foster–Greer–Thorbecke poverty index and Tobit regression at p=0.05. Mean per capita household expenditure at 1980 prices was lowest (N89.75 ± N60.31) in 1996 and highest (N1,124.78 ± N1,072.00) in 2004. The IP decreased between 1980 (0.2389) and 1985 (0.2111), increased in 1992 (0.2371), then decreased in 1996 (0.2189) and 2004 (0.1874). The IP was highest in the southsouth in 1980 (0.2551), 1985 (0.1991) and 1996 (0.2147). In 1992, the southeast had the highest (0.2373) while the southwest was highest (0.1851) in 2004. The IP was lowest in the northcentral in 1980 (0.2019) and 1985 (0.1753). The southwest (0.2119) and northwest (0.1885) had the least values in 1992 and 1996 respectively. In 2004, the southsouth had the least IP of 0.1757. Among farming households, IP was highest (0.2169) in 1980 and lowest (0.1792) in 1985. Non-farming households had highest IP (0.2115) in 1980 and lowest IP (0.1806) in 2004. Male IP (0.2411) was higher than that of female (0.1792) in 1980. Also in 1996, IP was higher for male (0.1958) than female (0.1890). Except in 1992 when IP for educated households was higher (0.2140) than that of non-educated (0.2120), the other periods had non- educated being more polarised. Non-wage employed had higher IP over the periods with 0.1833 than wage employed 0.1799 in 2004. Polarisation increased with poverty level at N714.80 poverty line. A unit increase in age, household size and poverty significantly increased IP by 0.01%, 0.01% and 0.73% respectively. However, years of education and being married significantly decreased IP by 0.01% and 0.27% respectively. Income polarisation reduced among households over the periods but higher in the southern geopolitical zones as well as among farming households. Income redistribution policy should be based on poverty reduction.